A preliminary study of ultrasonographic appearances of gall bladder and biliary tract in clinically suspected biliary atresia - Yusoff, Wan Norhayati Wan (2006)
Topic : A Preliminary Study of the Ultrasonographic Appearances of Gall Bladder and Biliary Tract in Clinically Suspected Biliary Atresia. Background : Biliary atresia is one of the congenital anomalies that has high mortality rate which is characterized by a fibrosclerosing obliteration of the extrahepatic duct that uniquely presents in the first months of life. It is also the most frequent cause of chronic end-stage liver disease in children and accounting for 40 to 50 % of all pediatric liver transplants. Ultrasonography has been one of the diagnostic workouts, where early and specific diagnostic tools are important in achieving the correct diagnosis for better prognosis of patients. Methods and Materials : This is a retrospective cross sectional study, involving 32 clinically suspected biliary atresia infants with 32 normal infants as a control group. The aim of this study is to compare the gall bladder appearance and it measurements between disease and control group. Triangular cord was assessed in the porta hepatis from hepatobiliary ultrasonography done from January 2003 till December 2005 in HUSM between clinically suspected biliary atresia infants and normal control group. Results : Most of the infants were term infants with normal birth weight. There was no significant difference noted between sex, race, gestational age and day of ultrasound performed between the clinically suspected biliary atresia andnormal control subject. Significant difference was noted between the gall bladder wall thickness, length and width between the two group with p value of 0.009, 0.001 and 0.022 respectively. Conclusion : There is a significant difference noted in the gall bladder length, width and wall thickness between the clinically suspected biliary atresia and normal control group. Gall bladder was present in 84.4 % of cases and triangular cord sign was present in 20.1 % in clinically suspected biliary atresia infants.